Spatial statism: Afterword to the Foreword by Ran Hirschl and Ayelet Shachar. (21st May 2020) - Doyle, Oran
Abstract: "Spatial statism" challenges us to pay greater attention to the spatial dimension of public law and provides a critique of how states dominate that geographic space. In this Afterword, I suggest that the spatial dimension of public law can be helpfully understood as a special case of the geographic dimension of law in general. State domination of geographic space warrants critical attention, particularly in the context of migration regulation. But we must also pay attention to the advantages of states as the primary locus of constitutional authority.